Educational and Literary Development of Kashmir in Dogra Era - Butt, Ghulam Hassan; Aziz, Kh. Zahid (sourcecoder, 2023)
The State of Jammu and Kashmir having an area, 84471 Square miles, was purchased by Mahraja Gulab Singh in March 16, 1846 in 750000 Nanak Shai from British government. The sale deed was signed between Mahraja Gulab Singh and the British government. Mahraja Gulab Singh ruled the State from 1846 to 1857. After his death his son Mahraja Ranbeer Singh became the ruler of Kashmir. Mahraja Ranbeer Singh died in 1885 and his son Mahraja Partap Singh became the ruler. He ruled the State for a long period and died in 1925. After his death his nephew Hari Sing became the last ruler who ruled till 1947. During the Dogra Era promotion of literature and educational development was observed that will be discussed in this paper. The cultural promotion and famous literary work done in this period will be elaborated.